2008
DOI: 10.1210/jc.2008-1297
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adenosine 5′-Monophosphate-Activated Protein Kinase as a Mechanism of Visceral Obesity in Cushing’s Syndrome

Abstract: Our data suggest that glucocorticoids inhibit AMPK activity in adipose tissue, suggesting a novel mechanism to explain the deposition of visceral adipose tissue and the consequent central obesity observed in patients with iatrogenic or endogenous Cushing's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 22 publications
2
59
0
2
Order By: Relevance
“…These can be combined with agents that increase postprandial insulin secretion such as sulphonylureas and meglitinides. The effect of metformin (and possibly thiazolidinediones) on fat tissue and other organ AMP-activated protein kinases (AMPK) could be beneficial (44,45). Pioglitazone may have a potential negative effect on heart and bone (46).…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 99%
“…These can be combined with agents that increase postprandial insulin secretion such as sulphonylureas and meglitinides. The effect of metformin (and possibly thiazolidinediones) on fat tissue and other organ AMP-activated protein kinases (AMPK) could be beneficial (44,45). Pioglitazone may have a potential negative effect on heart and bone (46).…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 99%
“…is hypothesis is based on the simple observation that patients with Cushing's syndrome develop central obesity, which improves with the resolution of hypercortisolism [10,11].…”
Section: Original Research © 2011 Cimmentioning
confidence: 99%
“…Cross-sectional studies showed that morning cortisol levels are signi cantly correlated with the symptoms of metabolic syndrome, such as visceral obesity, high blood pressure and a poor lipid pro le [3][4][5]. Further studies suggest that metabolic syndrome is a less profound form of Cushing's syndrome, which is characterized by a rise in serum cortisol levels [4,[6][7][8][9].is hypothesis is based on the simple observation that patients with Cushing's syndrome develop central obesity, which improves with the resolution of hypercortisolism [10,11].It is known that men with metabolic syndrome are more frequently a ected with android obesity. Central fat distribution is signi cantly associated with increased cortisol levels [12,13], so it could be hypothesized that men with metabolic syndrome have a higher serum cortisol levels, due to increased abdominal obesity compared with women.…”
mentioning
confidence: 99%
“…Several physiological and pharmacological stimuli have been reported to stimulate rodent adipose tissue AMPK, including exercise, starvation, troglitazone and adrenaline (epinephrine) [10,[18][19][20], whereas AMPK is inhibited in response to ghrelin, corticosterone and a high-fat diet [21][22][23] in vivo. However, only one study has investigated AMPK activity in human adipose in vivo; in this study, insulin-resistant patients with Cushing's syndrome exhibited reduced AMPK activity compared with controls [24].…”
Section: Introductionmentioning
confidence: 97%